Website Design in Anggilowu Village - Hilfi Juawdesb; Sadr Lufti Mufreni (Procedia of Engineering and Life Science, 2021)
E-Government is a government website that provides information services to the public. Website is a technology service provided to facilitate the public in accessing the information needed. The creation of a website in Anggilowu Village aims to make it easier for people to obtain good and accurate information. Existing data is not centralized and managed manually. This makes a job ineffective and takes a long time. Therefore, the creation of a village website to facilitate communication between residents and the Anggilowu Village. The method used in this study was prototyping models. The result of this study is a design of a village profile website.